2017
DOI: 10.1186/s13705-017-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Technical and economic assessment of wind power potential of Nooriabad, Pakistan

Abstract: Background: Pakistan is a developing nation and heavily spends on the development of conventional power plants to meet the national energy demand. The objective of this paper is to investigate wind power potential of site using wind speed, wind direction, and other meteorological data collected over a period of 1 year. This type of detailed investigation provides information of wind characteristics of potential sites and helps in selecting suitable wind turbine. Methods: The site-specific air density, wind she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The main emphasis of present research is placed on the identification of success factors and then prioritization of most critical factors contributing towards the success of renewable energy projects. The potential of renewable energy resources in Pakistan has been estimated by a number of researchers Ali et al 2015;Arshad, Ahmed 2016;Asif 2009;Awan, Khan 2014;Ghafoor et al 2016;Gondal, Sahir 2010;Gondal et al 2017;Hulio et al 2017;Mirza et al 2003;PMD 2004;Raja et al 1996;Shahbaz et al 2015;Shakeel et al 2016;Sheikh 2009). However, their assessments were restricted to potentials and prospects of energy extraction from the renewable sources and their possible consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The main emphasis of present research is placed on the identification of success factors and then prioritization of most critical factors contributing towards the success of renewable energy projects. The potential of renewable energy resources in Pakistan has been estimated by a number of researchers Ali et al 2015;Arshad, Ahmed 2016;Asif 2009;Awan, Khan 2014;Ghafoor et al 2016;Gondal, Sahir 2010;Gondal et al 2017;Hulio et al 2017;Mirza et al 2003;PMD 2004;Raja et al 1996;Shahbaz et al 2015;Shakeel et al 2016;Sheikh 2009). However, their assessments were restricted to potentials and prospects of energy extraction from the renewable sources and their possible consumption.…”
Section: Introductionmentioning
confidence: 99%
“…the productivity of the wind machine). It is a critical criterion for choosing the appropriate wind turbine for the investigated area before discussing the economic feasibility of a wind energy plant [27]. As assured by Ahmed and Hanitsch [28], a wind turbine generator of 2 MW capacity and 100 m axis height is convenient for working in the town of Sidi Barrani to generate electricity, that based on the results of examining Weibull parameters for the mentioned site.…”
Section: Wind Turbine Productivity To Select the Best Fitmentioning
confidence: 99%
“…It shows that about 3% of the total land area of the country, which is approximately equal to 26, 400sq., is capable of generating 132GW of electricity. As a case study, the Noori-abad site in Pakistan was chosen for economic analysis and found that wind energy is produced at USD 0.02189/kW h at a height of 50m [83].…”
Section: A Wind Energymentioning
confidence: 99%